PBM PENGEMBANGAN USAHA CATERING KELOMPOK RAHAYU PRIMA SUMBER RAHAYU MOYUDAN SLEMAN YOGYAKARTA - Danang Yudhiantoro; Edy Nursanto; Rifki Indra Perwira (Dharma: Jurnal Pengabdian Masyarakat, 2022)
Catering Business Group The Rahayu Prima Sumber Rahayu Group is located in the hamlet of Goser, Sumber Rahayu, Moyudan Sleman Yogyakarta, and consists of women who are farmers who are engaged in the home catering business. The problem in the Catering Business Group of the Rahayu Prima Sumber Rahayu Group is developing a processed menu made from catfish and in developing its marketing area. This is due to the knowledge in food processing that comes from catfish, the less attractive packaging and the lack of marketing aspects. The purpose of this Pbm is to develop the Catering Business Group of the Rahayu Prima Sumber Rahayu Group which is economically independent in processing food menus made from catfish, as well as expanding the aspect of online marketing and improving people's welfare. The methods used to achieve these goals are in the form of interviews, training, and mentoring. PbM activities include: training and practice of processed products made from catfish, training and online marketing assistance and provision of packaging tools for processed food products made from catfish. The outputs of PbM activities are processed food products made from catfish, provision of marketing tools, website creation for online marketing of food products made from catfish, books on product processing and online marketing of food made from catfish, scientific publications in journals and proceedings as well as online news.